Seasonality, Epidemiology and Outcome of Congenital Diaphragmatic Hernia in South West of Iran - Masoud Dehdashtian; Shiva Bashirnejad; Arash Malekian; Mohammad Reza Aramesh; Mohammad Hasan Aletayeb (EL-Med-Pub, 2017)
Introduction: The pathogenesis of congenital diaphragmatic hernia (CDH) is not clear. Risk factors including environmental factors have been implicated in the pathogenesis of few congenital anomalies. We aimed to assess the effect of season on the incidence of CDH and mortality rate in the southwest of Iran. Material and Methods: In this retrospective study, the records of 60 patients with CDH who were admitted at Neonatal Intensive Care Unit (NICU) of Imam Khomeini Hospital of Ahvaz, Iran were evaluated. Results: Assuming that all the neonates born with CDH in the region reach this hospital, overall CDH prevalence rate was 1.09 per 10 000 total births. Conceptions in spring and summer in this region had statistically significantly higher incidence of CDH. Survival rate in the series was 41.6%. Conclusion: Seasonal variation has impact on the incidence of CDH. Mortality rate in neonates with CDH is still very high.